'All this way, all this money, for a five-minute procedure': barriers, mobilities, and representation on the US abortion road trip. Issue 2 (4th March 2023) - Engle, Olivia; Freeman, Cordelia
Abstract: The abortion road trip is a narrative device that has emerged in the last decade whereby the central plot of the story is the journey taken in search of an abortion. In this paper we analyze two young adult novels ( Girls on the Verge and Unpregnant ) and two films ( Grandma and Never Rarely Sometimes Always ) that follow adolescent girls traveling for abortions in the contemporary United States. Through the analysis of these four narratives, we argue that representations of the abortion road trip are novel for their focus on the barriers and politics of abortion access in the United States. While the representations do prioritize certain barriers over others, they mark an important shift in abortion discourse in popular culture. Instead of the 'drama' of the plot being the decision to have an abortion, it is increasingly other socio-politico-legal issues such as the lack of abortion clinics, the distance required to travel, legal rights for adolescents, the cost of the procedure, and the opinions of family and friends that take center stage. The focus on these structural, political barriers can help to educate audiences about the realities of abortion access in the US and move abortion discourse beyond the individual.